2008
DOI: 10.1021/ic800903s
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly and Characterization of a Novel 2D Network Polymer Containing a 60-Membered Organotin Macrocycle

Abstract: The reaction of 1-(4-carboxyphenyl)-5-mercapto-1 H-tetrazole with trimethyltin chloride in the presence of sodium ethoxide in benzene affords a novel 2D organotin network structure complex 1, which is an unusual organotin network containing a hexanuclear 60-membered organotin macrocycle. The complex has been characterized by elemental analysis, IR, and (1)H, (13)C, and (119)Sn NMR spectroscopy. Furthermore, we have also characterized the complex by X-ray crystallography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…1 H and 13 C NMR spectra were recorded on Varian Mercury Plus 400 spectrometer operating at 400, 100.6 and 149.2 MHz, respectively. The spectra were acquired at room temperature (298 K) unless otherwise specified; 13 Table 1 Selected bond lengths (Å) and angles (°) for complex 1.…”
Section: Materials and Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 H and 13 C NMR spectra were recorded on Varian Mercury Plus 400 spectrometer operating at 400, 100.6 and 149.2 MHz, respectively. The spectra were acquired at room temperature (298 K) unless otherwise specified; 13 Table 1 Selected bond lengths (Å) and angles (°) for complex 1.…”
Section: Materials and Measurementsmentioning
confidence: 99%
“…along with a carboxylate moiety [5][6][7][8][9][10]. In our previous work, we have reported several novel organotin complexes, including a macrocycle containing five tin nuclei with heterocyclic sulfur and nitrogen donor ligands and macrocyclic complexes containing three and eighteen tin nuclei with 2-mercaptonicotinic [11,12], as well as a novel 2D network polymer containing 60-membered organotin macrocycles [13]. To continue our research on organotin(IV) complex in this field, we chose another carboxylic acid ligand: 6-chloro-3-pyridineacetic acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Etaiw et al have reported a 3D supramolecular coordination polymer containing quinoxaline molecule, multidimensional supramolecular coordination polymers containing triphenyltin cation and CuCN, and a novel 3D-supramolecular coordination polymer based on CuCN, Ph 3 Sn cation and quinoxaline. In our previous work, we have reported several interesting organotin structures derived from multi-ligands through self-assembly, such as six-tin-nuclear 32-member macrocyclic complexes with o-mercaptobenzoic acid [23], a hexanuclear 60-membered macrocyclic complex with 1-(4-carboxyphenyl)-5-mercapto-1H-tetrazole and a 3D organotin polymer with phenylsuccinic acid [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more investigations have focussed on the synthesis of metal carboxylates of functionalized carboxylic acids with additional oxygen [7,8], sulfur [8,9], or nitrogen [10][11][12] donor groups.…”
Section: Introductionmentioning
confidence: 99%